(untitled) (Research, Society and Development, 2021)
The current paper gives a brief description of the role of ICTs in the inclusion of children with autism, ADHD, and dyslexia. Therefore, many researchers note that ICTs play a key role in inclusive education and help to bridge the digital gap. Thus, the research team of this paper presents specific examples of ICTs that aid children with learning difficulties. ICTs promote the equal participation of all students in the educational system and consequently prepare them for everyday life outside of the school. The use of ICTs and assistive technology in the educational processes will have positive effects in the inclusion of children with learning difficulties and help them solidify the newly acquired knowledge as well as develop their consciousness.